Th1/Th17-Related Cytokines and Chemokines and Their Implications in the Pathogenesis of Pemphigus Vulgaris - Rodolfo Pessato Timoteo; Marcos Vinicius da Silva; Camila Botelho Miguel; Djalma Alexandre Alves Silva; Jonatas Da Silva Catarino; Virmondes Rodrigues Junior; Helioswilton Sales-Campos; Carlo Jose Freire Oliveira (Mediators of Inflammation)
Pemphigus vulgaris (PV) is an autoimmune disease characterized by the presence of IgG autoantibodies against desmoglein-3. Despite the variety of findings, the chemokine and cytokine profiles that characterize the immune response in the disease are still poorly explored. Thus, 20 PV patients and 20 controls were grouped according to gender, ethnicity, place of residence, and clinical parameters of the disease. Then, the levels of chemokines and of Th1/Th2/Th17/Treg/Th9/Th22-related cytokines were assessed in the serum. PV patients had higher levels of inflammatory Th1/Th17 cytokines (IFN-γ, IL-17, and IL-23), as well as higher levels of CXCL8 and reduced levels of Th1/Th2-related chemokines (IP-10 and CCL11). However, no differences in the levels of IL-2, IL-6, TNF-α, IL-1β, IL-4, IL-9, IL-12, TGF-β, IL-33, MCP-1, RANTES, and MIP-1α were found between PV patients and their control counterparts. Furthermore, PV patients with skin lesions had higher serum levels of IL-6 and CXCL8 when compared to PV patients without lesions. Taken together, our findings describe the role of cytokines and chemokines associated with Th1/Th17 immune response in PV patients. Finally, these data are important for better understanding of the immune aspects that control disease outcome, and they may also provide important information about why patients develop autoantibodies against desmogleins.